Community Participation In The Implementation Of Siaran Mobile Application (Reporting And Assignment Application System) In South Tangerang City - Irawan, Enjang Pera (Advances in Social Sciences Research Journal, 2020)
This research is entitled community participation in the application of SIARAN mobile application (reporting and assignment application system) in South Tangerang City. The purpose of this research is how the community participates in utilizing the release mobile application (reporting and assignment application system) in South Tangerang City as a media for reporting when problems occur in the community. The supporting concepts and theories in this study are Government Public Relations, Community Participation, and Mobile-Based Smart City Applications. The method used in this research was qualitative descriptive research. The results showed that community participation was still not optimal, considering that the number of users of the SIARAN application had not met the set target. To increase community participation, the Tangerang City Government continues to socialize the importance of using the SIARAN application in various existing events and media reports. Apart from that, public participation is also encouraged by providing spaces for public participation so that people can participate in the planning and implementation of government policies by submitting inputs at various dialogue opportunities such as at the Development Planning Conference and various other socialization programs. Existence the dialogue between the community and the government, it is hoped that community participation will increase in the development process based on the smart city concept.